Altered hemostatic balance in favor of a procoagulant state in pregnant women with systemic lupus erythematosus - Antovic, Aleksandra; Lini, Daniele; Soutari, Nida; Lalic-Cosic, Sanja; Zickert, Agneta; Mc Nicholas, Andrea; Bremme, Katarina; Sennström, Maria; Franceschini, Franco; Svenungsson, Elisabet; Andreoli, Laura; Gunnarsson, Iva (Frontiers in Lupus, 2025)
Objectives: This study aimed to investigate hemostatic parameters in pregnant Systemic Lupus Erythematosus (SLE) patients in relation to the use of antithrombotic prophylaxis, preeclampsia (PE) and antiphospholipid antibody (aPL) status.Patients and methods: Thirty-four pregnant SLE patients, 80 pregnant healthy controls (HC) without PE were included. Patients with SLE were sampled during the first and third trimester of gestation. We analyzed fibrinogen, D-dimer and global hemostatic parameters including the overall coagulation potential (OCP), overall haemostatic potential (OHP) and the overall fibrinolysis potential (OFP). Fibrin structure was visualized using scanning electron microscopy (SEM).Results: Median age of the SLE patients was 33 (range 23-42) years and 31 (26-38) in the HC. The median disease duration was 10 (range 0-26) years. All but two SLE patients received prophylaxis with low dose acetylsalicylic acid (LDASA) and 11 received low molecular weight heparin (LMWH). OCP and OHP were significantly increased in SLE patients compared to HC (p<0.01). The levels of fibrinogen and D-dimer increased throughout pregnancies in SLE patients, but no differences were found in the third trimester compared to controls.Among patients treated with LMWH, OCP, OHP, and OFP were undetectable in two, both on high prophylactic dosage of whom one developed PE. OCP, OHP and OFP levels were not affected by low prophylactic doses of LMWH. Despite LDASA, preeclampsia occurred in four SLE patients (12.5%); of whom two also received high prophylactic LMWH dose. Five out of 32 (15.6%) patients had major bleeding complications at delivery. There were no thromboembolic complications.In this pilot study, pregnant SLE patients exerted a hypercoagulable state throughout pregnancy, as demonstrated by the global hemostatic parameters OCP and OHP, except two patients treated with full dosage of LMWH. The alterations in the coagulation system in SLE pregnancy need to be further studied with the aim to optimize treatment strategies.